Overcoming barriers to the creation of eLearning materials for GeoVUE' NeoGeographic outputs - Baird, K; Latif, F; Lin, Y; Argüello Casteleiro, M (2008)
GeoVUE is a research Node of the ESRC funded National Centre for eSocial Science, (NCeSS). It is working to explore new forms of Geographic research and practices. As this Geographic research embraces web2.0 approaches and technologies, so must the materials which are used to teach the next generation of geography students, especially in line with research which shows these students' technological expectations. This paper will look at how the barriers to the creation of these learning materials can be overcome.